IMMUNOLOGICAL EVALUATION OF INFLAMMATORY PROCESS IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE OF PROFESSIONAL ETIOLOGY - Івчук, В.В.; Коптєва, Т.Ю.; Ковальчук, Т.А. (World of Medicine and Biology, 2019)
The peculiarities of the activity of the inflammatory process and immunological parameters in patients with chronic obstructive pulmonary disease of occupational etiology were studied. The gradual growth of the studied parameters in all groups of patients with COPD of professional etiology, may indicate a gradual increase in the activity of the inflammatory process, along with the deepening of the severity of the course of the disease. The dynamics of the integration indexes for assessing immune status indicates that in the COPD of a professional etiology of varying degrees of severity an imbalance in the ratio of the cellular composition of the immune system occurs. During the course of this disease, significant impairment of the immune function occurs in the humoral segment.